The archaeology of prehistoric Arabia: adaptation and social formation from the Neolithic to the Iron Age - Magee, Peter (Cambridge world archaeology, 2014)
"Encompassing a landmass greater than the rest of the Near East and Eastern Mediterranean combined, the Arabian peninsula remains one of the last great unexplored regions of the ancient world. This book provides the first extensive coverage of the archaeology of this region from c. 9000 to 800 BC. Peter Magee argues that a unique social system, which relied on social cohesion and actively resisted the hierarchical structures of adjacent states, emerged during the Neolithic and continued to contour society for millennia later. The book also focuses on how the historical context in which Near Eastern archaeology was codified has led to a skewed understanding of the multiplicity of lifeways pursued by ancient peoples living throughout the Middle East"--